2021
DOI: 10.1111/dom.14299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whey protein plus vitamin D supplementation combined with progressive resistance training on glycaemic control, body composition, muscle function and cardiometabolic risk factors in middle‐aged and older overweight/obese adults with type 2 diabetes: A 24‐week randomized controlled trial

Abstract: Aim To determine the effect of whey protein plus vitamin D supplementation combined with progressive resistance training (PRT) on glycaemic control, body composition, muscle function and cardiometabolic risk factors in middle‐aged and older adults with type 2 diabetes (T2D). Materials and Methods In this 24‐week, randomized controlled trial, 198 overweight/obese adults (aged 50–75 years) with T2D undertook PRT (2‐3 days/week) with random allocation to whey protein (20 g each morning plus 20 g postexercise) plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…Other RCTs in older adults have revealed conflicting findings. After 24 weeks, Miller et al 27 showed no greater improvements of whey protein supplementation (increasing In our study, the mechanisms by which leucine-enriched whey protein isolate supplementation induced beneficial changes in LDL-cholesterol, fasting insulin, and HOMA-IR likely relates to the composite of the supplement (and particularly the high concentration of leucine ∼3-5 g per drink). Recent commentary 9,10 of pre-clinical and human work suggests whey protein exerts benefits on lipid metabolism and insulin resistance via interconnected pathways.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Other RCTs in older adults have revealed conflicting findings. After 24 weeks, Miller et al 27 showed no greater improvements of whey protein supplementation (increasing In our study, the mechanisms by which leucine-enriched whey protein isolate supplementation induced beneficial changes in LDL-cholesterol, fasting insulin, and HOMA-IR likely relates to the composite of the supplement (and particularly the high concentration of leucine ∼3-5 g per drink). Recent commentary 9,10 of pre-clinical and human work suggests whey protein exerts benefits on lipid metabolism and insulin resistance via interconnected pathways.…”
Section: Discussioncontrasting
confidence: 49%
“…After 24 weeks, Miller et al . 27 showed no greater improvements of whey protein supplementation (increasing total protein intake to ∼1.4 g/kg/day (average of training/non‐training days) plus vitamin D and resistance exercise on HbA1c or HOMA2‐IR when compared with resistance exercise alone in overweight/obese older adults with type 2 diabetes. Huang et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The selection process is presented in the flow diagram (Figure 1). Ten studies met the inclusion criteria (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were published between 2006 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the eligible studies investigated the effect of vitamin D (VD) ( 28 , 31 , 33 , 34 , 36 ). Different dosages of VD supplements were taken over different time spans.…”
Section: Resultsmentioning
confidence: 99%